2023
DOI: 10.1186/s12911-023-02359-1
|View full text |Cite
|
Sign up to set email alerts
|

Defining the content of a website on advance care planning in dementia: a focus group study with family and health professionals

Charlèss Dupont,
Tinne Smets,
Fanny Monnet
et al.

Abstract: Background Advance care planning (ACP) is a process that enables individuals to define goals and preferences for their future care. It is particularly relevant for people with dementia and their family. Interactive tools, such as websites, that encourage reflection, communication and/or documentation, may support this group in the ACP process. However, considering the specific needs of people with dementia, it is important to develop adapted tools for this population. This study was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this design, quantitative and qualitative data are analysed independently, and integrated at the point of interpretation. Previous research among family caregivers and health professionals, 23 and studies on web-based ACP interventions, 28 30 have shown that people with dementia and their families wish to engage in ACP at their own pace. 23 Hence, we estimated that an 8-week period would be a long enough time frame to allow participants to use the website.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this design, quantitative and qualitative data are analysed independently, and integrated at the point of interpretation. Previous research among family caregivers and health professionals, 23 and studies on web-based ACP interventions, 28 30 have shown that people with dementia and their families wish to engage in ACP at their own pace. 23 Hence, we estimated that an 8-week period would be a long enough time frame to allow participants to use the website.…”
Section: Methodsmentioning
confidence: 99%
“…First, we identified existing evidence on web-based ACP tools and defined the content of the ACP website with family caregivers and dementia experts. 23 Next, we developed the ACP website using the SCRUM method, which emphasises the role of feedback loops. 24 To improve the ultimate uptake of new interventions – such as our ACP website – by end-users, it is essential to systematically evaluate them before they are implemented.…”
Section: Introductionmentioning
confidence: 99%